2012
DOI: 10.1073/pnas.1115402109
|View full text |Cite
|
Sign up to set email alerts
|

An over-oxidized form of superoxide dismutase found in sporadic amyotrophic lateral sclerosis with bulbar onset shares a toxic mechanism with mutant SOD1

Abstract: Recent studies suggest that Cu/Zn superoxide dismutase (SOD1) could be pathogenic in both familial and sporadic amyotrophic lateral sclerosis (ALS) through either inheritable or nonheritable modifications. The presence of a misfolded WT SOD1 in patients with sporadic ALS, along with the recently reported evidence that reducing SOD1 levels in astrocytes derived from sporadic patients inhibits astrocyte-mediated toxicity on motor neurons, suggest that WT SOD1 may acquire toxic properties similar to familial ALSl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 30 publications
7
167
1
Order By: Relevance
“…Finally, accumulation of misfolded SOD1 has been reported by several groups also in sporadic ALS (27,(41)(42)(43)(44)(45)(46)(47), although other groups have reached the opposite conclusion (48)(49)(50)(51). The identification of MIF as a cytosolic chaperone that stimulates the folding or refolding of misfolded SOD1 and inhibits the aggregation of mutant SOD1 in vivo suggests new avenues for therapy in ALS, mediated by increasing intracellular MIF levels in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, accumulation of misfolded SOD1 has been reported by several groups also in sporadic ALS (27,(41)(42)(43)(44)(45)(46)(47), although other groups have reached the opposite conclusion (48)(49)(50)(51). The identification of MIF as a cytosolic chaperone that stimulates the folding or refolding of misfolded SOD1 and inhibits the aggregation of mutant SOD1 in vivo suggests new avenues for therapy in ALS, mediated by increasing intracellular MIF levels in the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized, misfolded SOD1 Wt is present in the intracellular inclusions in motor neurons of sporadic aLS patients [5,10]. Furthermore, recently it was shown that transgenic overexpression of SOD1 Wt causes aLS in mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, aggregation of mtSOD1 is associated with altered SOD1 maturation and intermolecular disulfide cross-linking of SOD1 * This work was supported, in whole or in part, by National Institutes of Health cysteine residues (17)(18)(19)(20). Of note, wtSOD1 cysteine residues can be modified by oxidation, which alters its structure, and has been proposed to be important in the pathogenesis of sporadic ALS (21)(22)(23)(24)(25).…”
Section: Alsmentioning
confidence: 99%